Salta’s elite during the state ´s formation process, 1850-1880. Regional trade and land distribution - Quintián, Juan Ignacio (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2012)
The following paper analyzes cadastres and provincial census taken between 1856 and 1875 to identify the salteño landowning elite. The study begins with the synthesis of the intraregional trade involving the landowning elite of Salta; the study describes the new tax structure created in 1855 to characterize wealthy families of the province. The analysis combines the detailed description of the sources used with the narrative of some facts that contribute to understand the complex relationship between the landowning elite and the state-formation process